Penggunaan Media Promosi melalui TikTok Marketing dalam Meningkatkan Produk d’Rens Donat Kentang Kediri - Rahmadewati, Finna Alleydayahya; Febriana, Ersa; Cahyo, Prasetyo Dwi; Neysa, Sema Yuniarista Elva; Aulia, Faiza Maziyatul; Bukhori, Fuadzi Al; Abdillah, Muhammad Roziq; RKarima, Rifki Zakiyyan; Shidiqy, Dhiya’u (Welfare : Jurnal Pengabdian Masyarakat, 2025)
d'Rens Production MSME is a culinary business in Kediri City that offers potato donuts as its main product, as well as a variety of other processed foods. Despite offering high-quality products, this business faces obstacles in digital marketing because its promotional efforts have not been able to reach a wide audience. This situation has resulted in low brand awareness and consumer interaction. To address these issues, community service activities were conducted by implementing a TikTok Marketing strategy through the involvement of internship students. The methods used included content planning, creative video production, and audience engagement publication and evaluation. The objective of this community service was to enhance the competitiveness and visibility of the business by optimally utilizing social media. Preliminary results show a 65% increase in engagement on the d’Rens TikTok account account by 65% in the first two months, as evidenced by the number of views, likes, and comments from consumers. This demonstrates that TikTok-based digital marketing strategies can be an effective alternative for MSMEs to expand their market and increase sales. With this activity, it is hoped that d'Rens Production will be able to manage its digital strategy independently so that it can develop sustainably.